KALINGA STYLE ARCHITECTURE OF TWO TEMPLES OF THE PRACHI VALLEY OF ODISHA IN EASTERN INDIA: A RECENT STUDY - Dr. Ratnakar Mohapatra (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The Prachi Valley in the state of Odisha is distinguished for its archaeological antiquities and religious sanctuaries in the Eastern part of India. The architectural designs and pattern of the extant temples of Prachi valley are the important parts of Odishan temple art in India. A good number of temples are existed in the different parts of the Prachi Valley and they represent the Kalinga style of temple architecture of Odisha in Eastern India. Out of various temples of Prachi valley, only two temples have been taken here for discussion considering their architectural significance. In fact, the artistic designs and architectural features of the Gramesvara temple of Lataharana and Ambika Temple of Kenduli of Prachi valley attract scholars, art historians and archaeologists to undertake more research works on these monuments. As the rare images / sculptures are found to be worshipped in the Gramesvara temple of Lataharana and Ambika Temple of Kenduli of the Prachi Valley, so these two ancient /old sites of Prachi Valley are the motivating study area for the scholars of art history as well as archaeologists. The extant images of Prachi valley were made by the artists of Kalingan School of artists of Odisha. The rare stone images found from the Gramesvara temple of Lataharana and Ambika Temple at Kenduli of Prachi valley epitomize the iconographic features of the Odishan classical art of the medieval period. The present article focuses on architectural style alongwith the religious importance of the above two temples of the Prachi valley of Odisha in Eastern India. Both the primary and secondary sources are meticulously utilized in the writing of this article.